MEMBANGUN PARIWISATA BERSAMA RAKYAT: KAJIAN PARTISIPASI LOKAL DALAM MEMBANGUN DESA WISATA DI DIENG PLATEAU - Raharjana, Destha Titi (Jurnal Kawistara, 2012)
Development as a process of life change should involve communities as intergral elements. People should not only be regarded as objects of development. The paradigm of the bottom up planning expects people to act as both the subject and object of development. In the context of the development of rural tourism, the planning process should involve the local communities from the beginning. Dieng Plateau as a tourist site has a diversity of attractions, and tourist-oriented villages are designed by local communities to complement the tourist attractions in Dieng. This Study focuses on the participation of the communities in western Dieng in developing tourist villages in their area.Various stages of the planning are completed collectively and then put into action together. By applying action research methods, this study has the following results: (1) the identi cation of problems in the development of rural tourism, (2) the mapping of the potential of rural tourism, and (3) the identi cation of potential inter-agency networking to support sustainable rural tourism in western Dieng.